2020
DOI: 10.1088/1742-6596/1657/1/012041
|View full text |Cite
|
Sign up to set email alerts
|

The correlation between students’ critical reading ability and their mathematical critical thinking

Abstract: This research aims at describing the relation between students’ ability in critical reading and their mathematical critical thinking at Mathematics Education Study Program of IKIP Siliwang. Critical Reading is one of basic skills for students to comprehend and value information. Reading comprehension skill will affect their study. This research is a descriptive study specifically correlational design. The subject is 40 students of Mathematics Education Study Program who have enrolled the General Indonesian Lan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 5 publications
0
3
0
1
Order By: Relevance
“…Critical reading abilities will further develop into critical reasoning and critical thinking. The study conducted by (Hidayati et al, 2020;Sari & Prasetyo, 2021;Wikanengsih et al, 2020) has also reported a correlation between critical reading and critical thinking that is significant. Therefore, 21st-century teachers should continue improving their critical reading abilities to form critical reasoning and critical thinking properly.…”
Section: Resultsmentioning
confidence: 93%
“…Critical reading abilities will further develop into critical reasoning and critical thinking. The study conducted by (Hidayati et al, 2020;Sari & Prasetyo, 2021;Wikanengsih et al, 2020) has also reported a correlation between critical reading and critical thinking that is significant. Therefore, 21st-century teachers should continue improving their critical reading abilities to form critical reasoning and critical thinking properly.…”
Section: Resultsmentioning
confidence: 93%
“…From Figure 6 above, the question sheet instrument is the most commonly used by examiners to collect data on students' critical thinking skills. In essence, critical thinking skills are ways of thinking that can be assessed based on students' answers to high-level questions (Susilo et al, 2020;Wikanengsih et al, 2020). Some researchers did not inform whether the instrument used had been tested for reliability and validity regarding the test used as the main technique in collecting data.…”
Section: Percentage Of Each Treatment Researchmentioning
confidence: 99%
“…Kompetensi berpikir kritis dan pemecahan masalah merupakan salah satu kompetensi yang dibutuhkan di era 21 tahun ini kompetensi kreativitas, komunikasi, dan kolaborasi (Wikanengsih, 2020). Beberapa penelitian yang sudah dilakukan menyatakan bahwa penelitian berpikir kritis sangat mampu untuk meningkatkan kegiatan pembelajaran bahasa di Perguruan Tinggi salah satunya penelitian (Tusino, 2020) Hasil penelitian menunjukkan bahwa pengajaran bahasa berbasis tugas hibrida efektif untuk meningkatkan kinerja menulis siswa EFL.…”
Section: Landasan Ontologi Bahasaunclassified